Alcohol‐use disorders during and within one year of pregnancy: a population‐based cohort study 1985–2006. Issue 6 (19th February 2013) - O'Leary, CM; Halliday, J; Bartu, A; D'Antoine, H; Bower, C
<x xml:space="preserve">Abstract</x> Objectives To examine alcohol‐use disorders in pregnant women and the extent of under‐reporting. Design Population‐based cohort study. Setting Western Australia. Population Women with a birth recorded on the Western Australian Midwives Notification System (1985–2006). Methods Mothers with an International Classification of Diseases 9/10 alcohol‐related diagnosis, indicating heavy alcohol consumption, recorded on population‐based health datasets (non‐Aboriginal n = 5839; Aboriginal n = 2583) were identified through the Western Australian data‐linkage system. This 'exposed' cohort was frequency matched (on maternal age, year of birth of offspring, Aboriginal status) with comparison mothers without an alcohol‐related diagnosis (non‐Aboriginal n = 33 979; Aboriginal n = 8005). Main outcome measures Trends in maternal alcohol diagnoses in relation to pregnancy for non‐Aboriginal and Aboriginal women. The proportion of children diagnosed with fetal alcohol syndrome (FAS) who had a mother with an alcohol diagnosis recorded during pregnancy. Results The proportion of Aboriginal mothers in Western Australia with an alcohol diagnosis (23.1%) is ten times greater than for non‐Aboriginal mothers (2.3%). There has been a six‐fold increase in the percentage of non‐Aboriginal births with a maternal alcohol diagnosis recorded during pregnancy and a 100‐fold increase for Aboriginal births. Around 70% of the mothers of children diagnosed with FAS did not have an alcohol diagnosis recorded during pregnancy and 18% of the mothers had no record of an alcohol diagnosis. Conclusions Maternal alcohol exposure during pregnancy is significantly under‐ascertained. Given the severe risks to the fetus from heavy prenatal alcohol exposure, assessment and recording of alcohol use should be routinely undertaken in maternity and other health settings.